The expression of spinal methyl-CpG-binding protein 2, DNA methyltransferases and histone deacetylases is modulated in persistent pain states - Tochiki Keri K; Cunningham Joel; Hunt Stephen P; Géranton Sandrine M (Molecular Pain, 2012)
Abstract Background DNA CpG methylation is carried out by DNA methyltransferases and induces chromatin remodeling and gene silencing through a transcription repressor complex comprising the methyl-CpG-binding protein 2 (MeCP2) and a subset of histone deacetylases. Recently, we have found that MeCP2 activity had a crucial role in the pattern of gene expression seen in the superficial dorsal horn rapidly after injection of Complete Freund's Adjuvant (CFA) in the rat ankle joint. The aim of the present study was to analyse the changes in expression of MeCP2, DNA methyltransferases and a subset of histone deacetylases in the superficial dorsal horn during the maintenance phase of persistent pain states. In this process, the cell specific expression of MeCP2 was also investigated. Results Using immunohistochemistry, we found that neurones, oligodendrocytes and astrocytes expressed MeCP2. Microglia, oligodendrocyte precursor cells and Schwann cells never showed any positive stain for MeCP2. Quantitative analyses showed that MeCP2 expression was increased in the superficial dorsal horn 7 days following CFA injection in the ankle joint but decreased 7 days following spared nerve injury. Overall, the expression of DNA methyltransferases and a subset of histone deacetylases followed the same pattern of expression. However, there were no significant changes in the expression of the MeCP2 targets that we had previously shown are regulated in the early time points following CFA injection in the ankle joint. Finally, the expression of MeCP2 was also down regulated in damaged dorsal root ganglion neurones following spared nerve injury. Conclusion Our results strongly suggest that changes in chromatin compaction, regulated by the binding of MeCP2 complexes to methylated DNA, are involved in the modulation of gene expression in the superficial dorsal horn and dorsal root ganglia during the maintenance of persistent pain states.